UPAYA KOMISI PEMILIHAN UMUM (KPU) KOTA SURABAYA DALAM MENGELOLA DATA PEMILIH UNTUK MENINGKATKAN EFEKTIVITAS KINERJA PEMILU - Ismail Ismail; Ali Fahmi; Saroh Purnama Sari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2022)
The General Election (Pemilu) is a democratic party conducted by a country. One of the countries that uses democracy is the State of Indonesia where the highest system of sovereignty and power lies in the hands of the people. Voter data in the Permanent Voter List (DPT) will continue to occur in the implementation of general elections which are held every 5 years, thus creating problems that occur in the collection and management of voter data. This study aims to determine the extent of efforts in managing voter data at the Surabaya City Election Commission to support the successful implementation of tasks. Then knowing what factors are supporting and hindering in managing voter data at the Surabaya City Election Commission so as to find out the extent of the influence of factors on task success. To find out the extent of the success of the tasks carried out by the Surabaya City KPU in Improving the Effectiveness of Election Performance. This study uses qualitative research methods. Qualitative research in data collection techniques uses in-depth interviews, documentation and literature to obtain relevant data and collect voter data information to understand how the General Election Commission (KPU) institution can improve the effectiveness of election performance. Sources of information in this study are those who have all thoughts about official activities to improve voter data management and improve the effectiveness of election performance, the subject of this research is ASN and Additional Personnel of the General Election Commission (KPU) of Surabaya City. The results show that activities in managing data voters at the Surabaya City KPU in order to support the general election have several stages of Standard Operating Procedure or SOP in the data input process. As for inputting or managing voter data, it also has inhibiting and supporting factors that affect the program. as well as the process of updating voter data such as New Additional Voter Data (DPTb), Transfer Voter Data (DPPh), Permanent Voter Data (DPT) in order to produce good voter data as reference material in the next general election in order to improve the effectiveness of election performance. Voter data is used as a reference for continuous general elections in order to improve the effectiveness of election performance.